Enhancing the solubility of SARS-CoV-2 inhibitors to increase future prospects for clinical development - Kuhn, Ariel J.; Outlaw, Victor K.; Marcink, Tara C.; Yu, Zhen; Mears, Megan C.; Cajimat, Maria N.; Kreitler, Dale F.; Cleven, Payton R.; Mook, Jee Ching; Bente, Dennis A.; Porotto, Matteo; Gellman, Samuel H.; et al. (Journal of virology, 2025)
Despite the existence of vaccines for SARS-CoV-2, the constant evolution of new variants and the occurrence of breakthrough infections highlight the need for new and effective antiviral approaches. We have shown that lipopeptides designed to bind a conserved region on the SARS-CoV-2 spike protein can effectively block viral entry into cells and thereby block infection. To support the feasibility of using this approach in humans, we re-designed these lipopeptides to be more soluble, using information about the structure of the spike protein interacting with the peptides to modify the peptide chain. The new peptides are effective against both SARS-CoV-2 and MERS. The lipopeptides described here could serve as treatment for people who are unvaccinated or who experience breakthrough infections, and the approach to increasing solubility can be applied in a broad spectrum approach to treating infections with emerging viruses.